Pemanfaatan Limbah Minyak Jelantah Menjadi Sabun Sebagai Upaya Pengendalian Limbah Domestik Masa Pandemi Covid-19 - Arlina Phelia; Galuh Pramita; Bertarina; Ashruri; Felly Misdalena (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
The need for food during the Covid-19 pandemic in Bandar Lampung is increasing, one of which is cooking oil, which is usually used by housewives daily for cooking purposes. One of the district that has experienced an increase in the use of cooking oil is the Kedamaian district. People living in these areas still not know the dangers or benefits of used cooking oil waste and most of them work as culinary traders and tempe traders. This activity is carried out by training and socialization of waste used cooking oil into environmentally friendly bar soap. In addition, this activity is expected to increase public understanding especially housewives, about the importance of handling domestic waste, the development processing alternatives from used used oil as raw material, and trigger social and economic quality improvements for the community in Kedamaian district.